Formulasi Sediaan Krim Sari Buah Mangga Harum Manis (Mangifera Indica L.) Sebagai Pelembab Kulit Dan Tabir Surya - Putri Elvia Sari; Mamik Ponco Rahayu; Anita Nilawati (Jurnal Farmasi Indonesia, 2025)
UV rays can cause wrinkles, dryness and spots so the skin needs sunscreen nutrition. Sweet fragrant mango fruit contains flavonoids, tannins, and vitamin c as potential sunscreen. This study aims to formulate mango juice as a moisturising and sunscreen cream preparation in the form of hand cream. Mango fruit juice was extracted using a juicer and dried with a freeze dryer, then formulated into creams with concentrations of 2.5%; 5%; 7.5%; 10%. The preparation was evaluated for physical quality and tested for anti- irritation activity, moisture, and SPF value using a spectrophotometer. Data were statistically analysed using SPSS One Way Anova. The results showed that mango juice contains flavonoids, tannins, and vitamin C compounds. The cream formula fulfils the physical quality evaluation requirements of the preparation, does not irritate and has skin moisture activity. Formula 4 is the most effective cream preparation in moisturizing the skin with a moisture percentage of 72% but does not have SPF activity.